Agricultura familiar superando desafios em contextos concorrenciais: estudo de caso realizado na região noroeste e Missões do estado do Rio Grande do Sul - Pérez, Flávia Ines Carvajal (2011)
The family farms and small agroindustry family are of fundamental importance in rural development in Brazil, due to its role in food production and income generation. This study was conducted with the Central Cooperative Family Farming Ltda. - UNICOOPER, along with associated located in the municipalities in the northwest and Missions of the State of Rio Grande do Sul. The Cooperative is highlighted by work being done as a facilitator of commercialization, seeking new markets for the commercialization of alternative products to soybeans from family farms in the region, besides participating in the More Food Program of the Federal Government - PAA for school lunches. This study aimed to analyze the organizational setting in which the network UNICOOPER operates, how it really benefits family farmers and agroindustries who is inserted, and how to overcome the challenges UNICOOPER in competitive contexts with sustainable development. The methodology consists of field research and literature. For data collect was carried out semi-structured interviews with leaders of UNICOOPER, associated cooperatives and actors involved. The configuration with which the Central Cooperative has been working is innovative because it is characterized by a network of cooperatives and cooperatives differs from the traditional form of action, which involves the organization of producers, with the help of technical assistance for the production of differentiated products. Through interviews, it was possible to identify the characteristics of each cooperative, competitive strategies, and factors limiting and potencializantes commercialization, motivating factors for entering the network, challenges and future prospects of the organization. There is evidence that in UNICOOPER, strategies are emerging, and has great competitive strength generic strategy is differentiation. The most a associated cooperatives emerged and is being made possible due to the PAA. The work that has UNICOOPER performs some challenges that need to be overcome for the continuity and viability of the network, such as trained staff, motivated, technical assistance, help in the legalization of agroindustry, management and logistics. The UNICOOPER, along with the associated cooperatives, enables the family farmers, helping organize them to increase production, enabling the commercialization of these products and thus contributing to the permanence of the same field, by generating income for their families.